Mixing cations with different alkyl chain lengths markedly depresses the melting point in deep eutectic solvents formed from alkylammonium bromide salts and urea. Issue 15 (6th February 2017) - Chen, Zhengfei; Greaves, Tamar L.; Warr, Gregory G.; Atkin, Rob
Abstract : Mixing cations with different alkyl chain lengths markedly depresses the freezing point in deep eutectic solvents. Abstract : The melting point of a deep eutectic solvent formed from a ternary mixture of ethylammonium bromide (EABr), butylammonium bromide (BABr) and urea is 10 °C, which is almost 40 °C lower than the melting points of binary DESs formed from either EABr:urea or BABr:urea mixtures. This reveals a new route to prepare room temperature DESs via mixing different cations.